The Effectiveness Combination of Maggot with Commercial Feed on Growth, Structure of Intestine and Skeletal Muscle Mutiara Catfish - Haris Setiawan; Ichsan Luqmana Indra Putra; Ridwan Alfatah; Akhmad Nizzar Nasikhudin (Department of Aquaculture, 2022)
Maggot (Black soldier fly larvae) as an alternative source of protein on feed can increase fish productivity. The research aims to study maggot flour as an alternative source of protein in feed on the growth, structure of the intestine organs and skeletal muscles of Mutiara catfish (Clarias gariepinus Burchell, 1822). The research used 144 Mutiara catfish that were kept for 21 days. The research used a completely randomized design consisting of 4 groups, namely 0% maggot in feed (Control), 25% maggot in feed (P1), 50% maggot in feed (P2), 75% maggot in feed (P3). The parameters consist of the growth, the structure of intestine and skeletal muscle of Mutiara catfish. Growth observations consist of measurements of the absolute length and weight of the fish. Intestine observations consisted of length and weight, as well as tissue structure consisting of villi height, crypt depth, villi / crypt ratio and villi area area. Skeletal muscle observations consist of muscle weight and tissue structure consisting of the diameter and area of muscle fibers. Data analysis was performed with one-way anova, followed by the Duncan Test. The results showed that 75% maggot feed gave significant results on absolute weight, structure of intestine and muscle organs compared to other treatments (P <0.05). The absolute length did not provide a significant difference between treatments (P> 0.05). The conclusion shows that 75% maggot feed can be used as an alternative source of feed protein because it can increase the growth, structure of the intestine organs and skeletal muscles of the Mutiara catfish.